2017
DOI: 10.1039/c6gc03147a
|View full text |Cite
|
Sign up to set email alerts
|

Greener solvents for solid-phase synthesis

Abstract: The use of a range of green solvents to swell a diverse range of resins used in solid-phase synthesis is investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
82
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 98 publications
(82 citation statements)
references
References 54 publications
0
82
0
Order By: Relevance
“…Of note, various research groups have screened greener solvents for SPPS [35][36][37][38]. The results issuing from these studies indicate that a reduction of the cumulative Number of Hazard Phrases in both the coupling and deprotection steps may be accessible by choosing more appropriate solvents than DMF.…”
Section: Comparison Based On the Environmental Impactmentioning
confidence: 96%
“…Of note, various research groups have screened greener solvents for SPPS [35][36][37][38]. The results issuing from these studies indicate that a reduction of the cumulative Number of Hazard Phrases in both the coupling and deprotection steps may be accessible by choosing more appropriate solvents than DMF.…”
Section: Comparison Based On the Environmental Impactmentioning
confidence: 96%
“…Racemization of the activated amino acids in PC was negligible and the methodology was applied to the synthesis of the nonapeptide bradykinin (an inflammatory mediator; Figure ) . The authors have also reported extensive and in‐depth studies screening different green solvents and their ability to swell the most commonly used resins . Interestingly though, the authors report that the piperidine cocktail needs to be freshly prepared, but no data on the stability of piperidine in PC are given.…”
Section: Attempts To Make a Greener Protocolmentioning
confidence: 99%
“…[49] The authors have also reported extensivea nd in-depths tudies screening different green solvents and their ability to swell the most commonly used resins. [50] Interestingly though, the authors report that the piperidine cocktail needs to be freshly prepared, but no data on the stability of piperidine in PC are given.T he most recent report on the greening of peptide synthesis comes from Novartis Pharmaceutical. [51] Scientists at Novartis screened as eries of solvents and provided in-depthi nformationr egarding all challenging steps of the synthesis.…”
Section: Greener and Safer Solventsmentioning
confidence: 99%
“…[19] This is in contrast to at raditional ketone,s uch as acetone, that tend to exist predominantly in the ketone form in aqueouss olutions.T he equilibrium also can be shifted in the presence of 1,2-diols, which form cyclic acetals outo f the ketone moiety. [49] Hoping to take advantage of the strong solvency power of Cyrene, anumber of research groups have investigated its use as as olvent for synthetic transformations. An increased understandingo ft his equilibrium-specifically regarding the pH, temperature, and Scheme4.Nucleophilic additionst oC yrene (2).…”
Section: Use Of Cyrene As Abio-available Solventmentioning
confidence: 99%